2017
DOI: 10.1080/15563650.2016.1271125
|View full text |Cite
|
Sign up to set email alerts
|

The toxicology of zinc chloride smoke producing bombs and screens

Abstract: Intoxication with clinical signs mainly took place in war situations and in military and fire emergency training sessions in enclosed spaces. Symptoms follow a biphasic course mainly characterised by dyspnoea, coughing and lacrimation, related to irritation of the airways in the first six hours, followed by reappearance of early signs complemented with inflammation related signs and tachycardia from 24 h onwards. Acute respiratory stress syndrome developed in severely affected individuals. Chest radiographs di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…For dermal toxicity, the small quantity of information available for Zn for the bulk is not correlated with significant adverse events; however, it has been observed that ZnO NPS can be overused through makeup, sunscreen, and ointments, having an LD50 greater than 2000 mg/kg per body weight [223] , [224] , [225] , [226] . Inhalational toxicity can vary reliant on the compound involved and the duration of the exposure; for example, individuals who breathe Zn-containing smoke (ZnCl 2 and/or ZnO), mostly from industrial processes or military activities, can ultimately experience an acute condition of ARDS-like [227] . The permissible exposure limit in the workplace is 5 mg/m 3 for ZnO [228] .…”
Section: Zn As An Essential Element In Emerging Virus Mediated-respir...mentioning
confidence: 99%
“…For dermal toxicity, the small quantity of information available for Zn for the bulk is not correlated with significant adverse events; however, it has been observed that ZnO NPS can be overused through makeup, sunscreen, and ointments, having an LD50 greater than 2000 mg/kg per body weight [223] , [224] , [225] , [226] . Inhalational toxicity can vary reliant on the compound involved and the duration of the exposure; for example, individuals who breathe Zn-containing smoke (ZnCl 2 and/or ZnO), mostly from industrial processes or military activities, can ultimately experience an acute condition of ARDS-like [227] . The permissible exposure limit in the workplace is 5 mg/m 3 for ZnO [228] .…”
Section: Zn As An Essential Element In Emerging Virus Mediated-respir...mentioning
confidence: 99%
“…The great release of pro-inflammatory cytokines and apoptosis were the results of ZnCl 2 smoke exposure (El Idrissi et al., 2017 ). Inflammation and apoptosis further strengthen ALI/ARDS (Vadász & Sznajder, 2017), resulting in serious damage of pulmonary blood vessels, increased permeability, and a large amount of plasma proteins and active substances infiltrating to the interstitium and alveoli of the lung (Yoneshige et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…pletely recovered soon after the administration of methylprednisolone (125 mg/day for 3 days) and subsequent oral prednisolone (30 mg/day for 5 days) (Picture 2). Zinc chloride-based smoke bombs are used in fire and military drills, but a few cases of acute respiratory failure during a fire-fighting drill have been reported (1,2). Physicians should keep in mind that acute respiratory failure can occur even 24 hours after toxic gas inhalation.…”
Section: Picturementioning
confidence: 99%